Macrophage-Mediated Bone Formation in Scaffolds Modified With MSC-Derived Extracellular Matrix Is Dependent on the Migration Inhibitory Factor Signaling Pathway - Deng, Moyuan; Tan, Jiulin; Dai, Qijie; Luo, Fei; Xu, Jianzhong (Frontiers in Cell and Developmental Biology, 2021)
Recently the role of macrophages on osteogenesis of mesenchymal stem cells (MSCs) is brought to focus. On the other hand, the cross-talk between macrophages and MSCs confirms that the paracrine molecules derived from macrophages are also carefully regulated by MSCs. Human umbilical cord mesenchymal stem cells (hucMSCs) could reduce secretions of inflammatory factors from macrophages for improving injury healing. hucMSC-derived extracellular matrix (hucMSC-ECM) exhibited nature similar to hucMSCs. It has been demonstrated that hucMSC-ECM possess considerable effects on reducing inflammatory response of macrophages, while the role of hucMSC-ECM on the expression of macrophage-derived paracrine osteogenic molecules is unclear. Here, we presented the decalcified bone scaffolds modified by hucMSC-derived extracellular matrix (DBM-ECM) which maintained multiple soluble cytokines from hucMSCs including macrophage migration inhibitory factor (MIF). Compared with DBM, the DBM-ECM scaffolds induced bone formation in a macrophage-depending manner by an improved heterotopic ossification model in severe combined immunodeficiency (SCID) mice with macrophage depletion. Macrophages cocultured with the DBM-ECM expressed four osteoinductive cytokines (BMP2, FGF2, TGFβ3 and OSM), which were screened out by RNA sequencing, qPCR and western blot. The conditioned medium from macrophages cocultured with the DBM-ECM improved osteogenic differentiation of hBMSCs and activated CD74/CD44 signal transduction including phosphorylation of P38 and dephosphorylation of c-jun. Furthermore, the inhibitory effects of the DBM-ECM scaffolds with knockdown of MIF on osteogenesis in vitro and in vivo revealed that macrophage-mediated osteogenesis depends on MIF/CD74/ P38 signal transduction. This study indicates that the coordinated crosstalk of macrophages and MSCs play a key role on bone regeneration induced by scaffolds, with the emphasis on the constructing macrophage-derived osteoimmunological microenvironment.